In vitro quantification of botulinum neurotoxin type A1 using immobilized nerve cell-mimicking nanoreactors in a microfluidic platform - Weingart, Oliver G.; Eyer, Klaus; Lüchtenborg, Christian; Sachsenheimer, Timo; Brügger, Britta; Oostrum, Marc van; Wollscheid, Bernd; Dittrich, Petra S.; Loessner, Martin J. (The analyst, 2019)
The bacterial toxin botulinum neurotoxin A (BoNT/A) is not only an extremely toxic substance but also a potent pharmaceutical compound that is used in a wide spectrum of neurological disorders and cosmetic applications. The quantification of the toxin is extremely challenging due to its extraordinary high physiological potency and is further complicated by the toxin's three key functionalities that are necessary for its activity: receptor binding, internalization-translocation, and catalytic activity. So far, the industrial standard to measure the active toxin has been the mouse bioassay (MBA) that is considered today as outdated due to ethical issues. Therefore, recent introductions of cell-based assays were highly anticipated; their impact however remains limited due to their labor-intensive implementation. This report describes a new in vitro approach that combines a nanosensor based on the use of nerve cell-mimicking nanoreactors (NMN) with microfluidic technology. The nanosensor was able to measure all three key functionalities, and therefore suitable to quantify the amount of physiologically active BoNT/A. The integration of such a sensor in a microfluidic device allowed the detection and quantification of BoNT/A amounts in a much shorter time than the MBA (<10 h vs. 2-4 days). Lastly, the system was also able to reliably quantify physiologically active BoNT/A within a simple final pharmaceutical formulation. This complete in vitro testing system and its unique combination of a highly sensitive nanosensor and microfluidic technology represent a significant ethical advancement over in vivo measures and a possible alternative to cell-based in vitro detection methods.
Gesehen am 31.10.2019